Effect of the main metabolite of afobazole M-11 on acute exudative inflammation and visceral pain in mice - E. A. Ivanova; T. A. Voronina (Фармакокинетика и Фармакодинамика, 2016)
In the model of peritonitis in mice induced by intraperitoneal injection of acetic acid the main metabolite of afobazole M-11 at doses of 1, 5 and 10 mg/kg per os reduces the intensity of the exudative stage of inflammation, but at doses of 20 and 40 mg/kg it exhibits no anti-inflammatory activity. The anti-inflammatory activity of M-11 at doses of 1, 5 and 10 mg/kg is less pronounced compared with diclofenac sodium 10 mg/kg. Evaluation of the influence of M-11 on visceral pain induced by inflammation demonstrated that the main metabolite of afobazole does not exhibit analgesic activity.